PENINGKATAN KUALITAS PEMBELAJARAN MATEMATIKA MELALUI METODE KOMPETISI ANTAR SISWA (KAS) PADA SISWA KELAS V DI SDN PAKINTELAN 03 (INCREASING MATHEMATIC INSTRUCTIONAL QUALITY BY STUDENTS COMPETITION AT FIFTH SDN PAKINTELAN 03) - Budiman, Arif (KREATIF, 2011)
The results of preliminary observations are carried out showed that the teachers are still not quite right in applying the methods of teaching and engage students in learning about. Exhaustiveness classical value only reached 39% by Minimum Criteria for Completeness is 70. The purpose of this research are: (1) improve the skills of classroom teachers SDN Pakintelan 03 in implementing the learning of mathematics, (2) increasing the activity of class V students of SDN 03 Pakintelan in implementing the learning of mathematics; improve student learning outcomes SDN Pakintelan 03 class V in the material eye math. The research was conducted in 03 road SDN Pakintelan Langkir, Pakintelan Village, District Gunungpati. The subject of this study were teachers and students of class V were 36 students. Variable of this study were (1) the skills of teachers, (2) student activity, and (3) student learning outcomes. Data collection techniques used were observation, test documentation, and records of activities. The results showed melelui KAS method can improve the teaching skills of teachers, student activities, and student learning outcomes. Percentage increase from the thoroughness student learning cycle by 76% I, II cycles by 89%. By looking at the data above it is advisable KAS method can be used by teachers in implementing the learning. The conclusions of this study is the KAS method can improve the skills of teachers; KAS methods can improve student learning activities; KAS methods can improve student learning outcomes. Therefore, it is recommended that teachers should be able to use traditional methods to improve teaching skills KAS, activities, and student learning outcomes. Key words: Quality of Learning, Methods KAS, Skills Teacher, Student Activities, Student Results.